Experimental investigation on the behaviour of reinforced concrete slabs strengthened with ultra-high performance concrete. (30th November 2017) - Yin, Hor; Teo, Wee; Shirai, Kazutaka
Highlights: UHPC is an excellent material suitable for strengthening concrete structures. Rehabilitated slabs show ductile failure mode with extensive deflection hardening. Retrofitted slabs show enhanced ultimate strength and stiffness. Thickness of UHPC layer is of great importance in determining the performance. Reinforced UHPC layer performs effectively, provided full bond development occurs. Abstract: Nine rectangular specimens were tested to investigate the behaviour of composite reinforced concrete (RC) slabs strengthened with ultra-high performance concrete (UHPC). The specimens were two series with various UHPC strengthening configurations. The first, a rehabilitation series, tested UHPC as patch material for repairing deteriorated concrete structures. The second, a UHPC overlay series, was used to retrofit soffits of RC members. The results showed that using the rehabilitation series, the UHPC reduced diagonal cracking and developed more flexural cracks as compared to RC slabs with no UHPC strengthening. The UHPC exhibited excellent energy absorption with extensive deflection hardening and ductility during the post cracking range. In the UHPC overlay series, each slab showed diagonal shear cracks and debonding modes. The UHPC overlay delayed the development of shear cracking. As the overlay thickness increased, the ultimate load increased; but the tendency for the UHPC to undergo fracture failure also increased.